Lower Class Representation in the Film Shoplifters - Setyaningsih, Wahyu Handayani; Saraswati, Tia (Pusat Kajian Humaniora FBS Universitas Negeri Padang, 2022)
This paper discusses the representation of the lower class and social reality in Japan through the film Shoplifters. This film is analyzed using the representation theory of Stuart Hall, with critical discourse analysis. The characters in the film are members of a marginalized social class who voice problems of poverty, stigmatization, family problems, and social alienation that on the other hand, are clashed with humanism values. The result of this study indicate that Shoplifters is a social critique that represent the lower class in Japan. The humanistic side shown by the characters through their attitude and dialogue becomes a paradox, as an effort to fight the stigmatization of the lower class that has taken root due to sociohistorical factors. Japan's advancement has impact on the alienation which they tried to overcome by building social cohesion in the form of a family.